2013
DOI: 10.1186/1746-6148-9-102
|View full text |Cite
|
Sign up to set email alerts
|

Pet ownership, dog types and attachment to pets in 9–10 year old children in Liverpool, UK

Abstract: BackgroundLittle is known about ethnic, cultural and socioeconomic differences in childhood ownership and attitudes to pets. The objective of this study was to describe the factors associated with living with different pet types, as well as factors that may influence the intensity of relationship or ‘attachment’ that children have to their pet. Data were collected using a survey of 1021 9–10 year old primary school children in a deprived area of the city of Liverpool, UK.ResultsDogs were the most common pet ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
66
2
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 23 publications
6
66
2
10
Order By: Relevance
“…This is in line with previous research on children/young people's attachment to pets conducted in the United States (Brown 2003) and in Kuwait (AlFayez et al 2003). However, our findings disagreed with a study conducted in the UK in which white children were not found to be more attached to pets than non-white children (Westgarth et al 2013). These differences between our results and Westgarth's (Westgarth et al 2013) study could be due to the difficulties of capturing cultural, historical and religious issues in a single variable in both studies and by the use of different attachment scales within the two studies.…”
Section: Demographic Variations In Ownership and Attachment To Petscontrasting
confidence: 57%
See 4 more Smart Citations
“…This is in line with previous research on children/young people's attachment to pets conducted in the United States (Brown 2003) and in Kuwait (AlFayez et al 2003). However, our findings disagreed with a study conducted in the UK in which white children were not found to be more attached to pets than non-white children (Westgarth et al 2013). These differences between our results and Westgarth's (Westgarth et al 2013) study could be due to the difficulties of capturing cultural, historical and religious issues in a single variable in both studies and by the use of different attachment scales within the two studies.…”
Section: Demographic Variations In Ownership and Attachment To Petscontrasting
confidence: 57%
“…However, our findings disagreed with a study conducted in the UK in which white children were not found to be more attached to pets than non-white children (Westgarth et al 2013). These differences between our results and Westgarth's (Westgarth et al 2013) study could be due to the difficulties of capturing cultural, historical and religious issues in a single variable in both studies and by the use of different attachment scales within the two studies. Furthermore, the mechanism underlying the relationship between ethnicity and children's attachment to their pets is presently unclear, one possible factor could be cultural differences and further research is needed to explore this.…”
Section: Demographic Variations In Ownership and Attachment To Petscontrasting
confidence: 57%
See 3 more Smart Citations